The Music of Elliott Carter - Schiff, David (Book collections on Project MUSE., 1998)
"The Music of Elliott Carter engages composers, performers, and critics and speaks to concert-goers, whether attuned to or alarmed by the formidable difficulty of Carter's music. David Schiff views the music from the perspective of the composer's development and relates his compositional techniques to those non-musical arts - contemporary American poetry in particular - with which Carter has been deeply involved. The volume benefits from Schiff's extensive discussions of Carter's works with their most noted performers, including Heinz Holliger, Oliver Knussen, and Ursula Oppens, and from the generous cooperation of the composer himself."--Jacket.